The Association between Macular Thickness and Axial Length in Myopic Eyes - Chung, Yeon Woong (Biomed Res Int, 2019)
PURPOSE: To investigate the relationship between macular thickness and axial length (AL) in myopic eyes. METHODS: We included 441 myopic eyes in this study and measured macular thickness at the fovea and in other macular regions, using optical coherence tomography. We got thickness difference indices (TDIs) which by definition are the values of thickness difference obtained by subtracting the foveal thickness from that of each macula sector to evaluate macular contour. We then analyzed the relationships between AL and foveal thickness and AL and the TDIs of each macular sector. RESULTS: In polynomial regression analyses, foveal thickness slope was relatively flat up to an AL of 25.5 mm and began to rise from 25.5–26.0 mm. The TDIs were also relatively flat up to AL of 25.5mm and started to show steepened negative slopes from around AL of 25.5 mm. When grouping myopia participants as high myopia or non-high myopia based on AL of 25.5mm, all macular indices of the high myopia group showed significant correlation with AL (all p values <0.01). But all indices of non-high myopia group had no significant correlation with AL. CONCLUSIONS: Average macular thickness profiles showed that appreciable changes started at an AL of 25.5mm.